Combining knowledge bases for small wins in peripheral regions. An analysis of the role of innovation intermediaries in sustainability transitions - Christoph Friedrich; Daniel Feser (Review of Regional Research, 2023)
A~growing number of economic geography scholars have discussed the spatial dimensions of sustainability transitions (STs), which entail radical changes in socio-technical systems to overcome societal, economic, and ecological problems. This involves innovation processes with a~broad range of distinctive actors. Innovation intermediaries, such as universities and research institutes, are needed to support and accelerate the transfer of knowledge. Nevertheless, little is known about the influence of such actors on the configuration of the knowledge bases required for STs. This article presents insights from 14~semi-structured interviews with experts conducted in a~regional innovation system (RIS) in East Germany. In cooperation with the Eberswalde University for Sustainable Development, we investigate four innovation intermediaries in the region of Eberswalde. The analytical framework links the concept of differentiated knowledge bases to small wins. Our results show that, first, in the Eberswalde region, the relevant actors involved in regional knowledge transfer focus predominantly on synthetic knowledge bases, such as experience-based knowledge of local area settings. Second, symbolic knowledge bases are crucial and often prerequisites for intermediary organizations to recombine knowledge bases and support the capability to innovate in regional knowledge transfer. Symbolic knowledge entails the ability to translate scientific findings to a~language that can be understood by the various actors in knowledge transfer. Third, changes in organizational structures complement changes in cultural–cognitive and normative institutions to support innovation on a~systemic level and foster change processes.
Keywords: D02; D80; O12:P48; Q56; R11; 910; Knowledge bases; Small wins; Knowledge transfer; Innovation intermediation; Sustainability transition